The Quality of Listening Skill of the EFL Students - Putri, Erawati Wiyono; Fauzan, Umar; Toba, Rostanti (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
Listening is often view as receptive or passive skill that hard to be measured. Nevertheless, listening is one skill that play a big role in enhancing students’ proficiency in English. Therefore, improving students’ quality in listening is important. According to Al-Musalli, there are four sub-skills involved in listening: 1) literal level, it involves three main types of skill: phonological, syntactic, and lexical skills; 2) inferential level, it related to the comprehension of the text; 3) critical level includes: making an appropriate judgment about the message, the speaker personality, and the topic, and; 4) creative level includes handling verbal and non-verbal communication strategies and responding in the proper way. All of these sub-skills can be used as the criteria to view students’ mastery level of listening. This research only applies three level as a benchmark to know students’ quality of listening, they are: literal, inferential, and critical. The objective of this research is to know the students’ quality in listening skill based on mastery level of listening. The research design is descriptive. The subjects of study are five students who meet the researcher’s criteria. Data collection technique in this research is using test of listening, interview, observation and documentation. The data is analyzed using the model of Miles and Huberman. After being collected, the data is verified using triangulation by method and another researcher. The result of this research shows that students at fourth semester of English Education Department in IAIN Samarinda located in inferential level of mastery listening skill which means their quality in listening can be categorized as good.